Multiculturalism as a Mediator of Ethnic Identity and National Identity among Javanese Adolescents - Priwati, Acintya Ratna; Putri, Adelia Krishna; Puri, Valendra Granitha Shandika; Ayuningtya, Annisa Ardi; Minza, Wenty Marina; Yuniarti, Kwartarini Wahyu (Makara Human Behavior Studies in Asia, 2021)
The development of national identity in a highly multicultural nation begins by identifying oneself to a particular ethnic group and realizing that multiculturalism is the bridge between both identities. This research aims to discover the link between national identity, ethnic identity, and multiculturalism in Indonesia, specifically for Javanese. This study utilized three measurement scales: (1) National Identity Scale to measure national identity; (2) Ethnic Identity Scale to measure the sense of belongingness to the Javanese ethnicity; and (3) Universal Diverse Orientation (UDO), to measure multiculturalism. This study's participants consist of 441 college students in Yogyakarta (male = 115; female = 326), ranging from 17 to 21. The regression analysis result shows that the mediation model supports this research hypothesis, namely that multiculturalism mediates the relationship between ethnic identity and national identity. Therefore, the current finding generates a new conception regarding the related theme.